(untitled) (Borneo Engineering & Advanced Multidisciplinary International Journal, 2025)
T-way interaction testing is a critical method in software testing, aimed at covering all t-way combinations of input parameters to identify interaction faults effectively. In recent years, from 2020 to 2024, numerous advanced t-way test generation strategies have been proposed to enhance test coverage, efficiency, and scalability. This research review examines comprehensively these recent strategies, providing an in-depth analysis of their objectives, methodologies and outcomes. Through a systematic literature review, this study evaluates the most prominent algorithms, highlighting significant improvements in test generation time, fault detection capabilities and applicability to complex software systems. The findings reveal notable advancements in addressing key challenges in combinatorial testing, offering insights into the evolving landscape of t-way test generation. This review concludes by summarizing the contributions of these recent strategies and proposing directions for future research to further enhance the effectiveness of t-way interaction testing.